2009
DOI: 10.1073/pnas.0903909106
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic analysis of amniotic fluid cell-free mRNA suggests that oxidative stress is significant in Down syndrome fetuses

Abstract: To characterize the differences between second trimester Down syndrome (DS) and euploid fetuses, we used Affymetrix microarrays to compare gene expression in uncultured amniotic fluid supernatant samples. Functional pathway analysis highlighted the importance of oxidative stress, ion transport, and G protein signaling in the DS fetuses. Further evidence supporting these results was derived by correlating the observed gene expression patterns to those of small molecule drugs via the Connectivity Map. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 46 publications
13
143
0
1
Order By: Relevance
“…Alterations in chromosome number, particularly trisomy 21, have been associated with elevated mitochondrial ROS, oxidative damage, diminished metabolism, and compromised resilience (Busciglio & Yankner, 1995; Coskun et al, 2016; Slonim et al, 2009; Zis et al, 2012) Here, we show that human DS HF and mouse Dp16 MEF display compromised mitochondrial function, oxidative stress, and activated Nrf2 antioxidant response. Furthermore, our results demonstrate that sustained Nrf2 stabilization is vital to maintain cell function in both DS and Dp16.…”
Section: Discussionmentioning
confidence: 49%
“…Alterations in chromosome number, particularly trisomy 21, have been associated with elevated mitochondrial ROS, oxidative damage, diminished metabolism, and compromised resilience (Busciglio & Yankner, 1995; Coskun et al, 2016; Slonim et al, 2009; Zis et al, 2012) Here, we show that human DS HF and mouse Dp16 MEF display compromised mitochondrial function, oxidative stress, and activated Nrf2 antioxidant response. Furthermore, our results demonstrate that sustained Nrf2 stabilization is vital to maintain cell function in both DS and Dp16.…”
Section: Discussionmentioning
confidence: 49%
“…3). The RNA was extracted, amplified, labeled and hybridized to either the Affymetrix U133A expression microarray (Larrabee et al 2005) or the Affymetrix GeneChip Human Genome U133 Plus 2.0 expression microarray (Slonim et al 2009;Koide et al 2011;Hui et al 2012aHui et al ,b, 2013aEdlow et al 2014;Massingham et al 2014). Despite the availability of more sophisticated expression microarrays, the U133 Plus 2.0 was chosen because of the need for compatibility with an essential downstream in silico tool, the Connectivity Map (Lamb et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, work from Slonim et al began to compare the development of second trimester fetuses with DS (caused by a full trisomy 21, T21) to that of healthy euploid fetuses (Slonim et al 2009). Expression microarray studies revealed a set of genes significantly differentially regulated between the seven age-and sexmatched pairs of fetuses.…”
Section: Genetic Disorders: Down Syndromementioning
confidence: 99%
“…She finds that gene activity is abnormal across the whole genome, not just on the extra chromosome, and even in genes needed for brain development 9 . She's also found that cells of fetuses with Down's incur damage from the by-products of metabolism, a condition known as oxidative stress 10 .…”
Section: Full Transcriptmentioning
confidence: 99%
“…She finds that gene activity is abnormal across the whole genome, not just on the extra chromosome, and even in genes needed for brain development 9 . She's also found that cells of fetuses with Down's incur damage from the by-products of metabolism, a condition known as oxidative stress 10 .This raises the provocative possibility of treating fetuses in the womb to ameliorate the cognitive impairment associated with Down's. To explore this, Bianchi's team compared transcriptome data from fetuses …”
mentioning
confidence: 99%